Evaluasi Perilaku Tenaga Vokasi Farmasi dalam Pemberian Informasi Obat di Apotek Jaringan X Se-Kota Pekanbaru Periode 2023-2024 - Fina Aryani; Septia Vanisa; Septi Muharni; Tiara Triagustini (Universitas Hamzanwadi, 2025)
Providing drug information is a crucial component in pharmaceutical services that aim to ensure the safe and rational use of medications. However, the practice of providing information by pharmacy technicians in pharmacies is often not optimal, especially in educational aspects related to patient safety. The purpose of this study was to evaluate the behavior of pharmacy technicians in providing drug information to patients at X Network Pharmacies in Pekanbaru City. This research is a quantitative descriptive study with a cross-sectional approach. A total of 32 pharmaceutical technicians became respondents, selected through a total sampling method. Data were collected using a structured observation sheet that included 15 indicators of drug information provision. Data were analyzed descriptively and presented in the form of a frequency distribution and a percentage. The results showed that the behavior of providing drug information by pharmaceutical technicians was still relatively low. Most of them only provided basic information, such as the name of the drug (78.12%), the time of consumption (71.87%), and instructions on how to use the drug (65.62%). Meanwhile, important information such as side effects, drug interactions, storage methods, and compliance with the use of drugs is almost not conveyed at all (≤10%). The behavior of pharmaceutical technicians in providing drug information still falls short of ideal pharmaceutical service standards. Continuous training, strict adherence to Standard Operating Procedures (SOPs), and supervision by the pharmacist-in-charge are necessary to enhance service quality and patient protection.